Polish Practice on Promulgation of International Agreements between Poland and the USSR, 1944–1960 (Polish Yearbook of International Law, 2024)
This article raises the issue of the proper publication of international treaties and their presence in the Polish legal system. The authors analyze this issue based on research conducted on Polish-Russian treaties from 1944–1960. Their research has shown that, during this period, only 11% of treaties were properly published. The research – conducted on a very limited subject: only bilateral agreements between Poland and the USSR – leads to the pessimistic conclusion that in Poland it is customary practice to refrain from publishing an international agreement in the Journal of Laws and that citizens do not have at their disposal a single official or unofficial source to reconstruct Poland’s current obligations, which may indeed directly concern them. Also this finding raises important questions about the accessibility and enforceability of international treaties in the Polish legal system. At the international level, the consequences of failing to publish an act and to ensure official promulgation can be much more serious. In the absence of information about published agreements, it is not possible to sufficiently and completely determine the obligations between states nor to reconstruct the relations binding them. It is also impossible to clearly determine which international agreements are still in force between countries, which are invalid and which have expired.